Tubal surgery - Bunster, Eduardo (2015)
The tubal pregnancy surgery should generally be radical in relation to the trunk and should not, with some exceptions, including the excision of the ovary. Conservative surgery of the pregnant horn is justified in cases where the patient has only one oviduct and want to have that family. In addition, the state of the patient and the trunk should allow this type of operation. In any case of pregnancy your trunk unaffected barium must be carefully examined and treated in accordance with what are, at least with a downward hydrotubation. Surgery of salpingitis will generally radical and the tube must be removed including interstitial portion. Only in cases where the conviction of the good condition of endosalpinx be taken may be made conservative tubal surgery. Genital TB even if clinically cured a contraindication for tubal plastic surgery in order to restore fertility. Endometriosis is an intimate your baria whose physiological impairment remain unknown mechanism that prevents a high percentage of pregnancy. Endometriosis surgery should be preceded and followed by a prolonged estrogen-progestogen treatment. Surgery tubal infertility because the author has given 39% of cases with pregnancies and 34.5% of children live among 23 operated in the past 15 years. Tubo-uterine implantation has supplied 33.3% of children living and 42.85% of pregnancies among 15 operated. The four patients salpingolisis this statistic has been successful with children living in two of them. Our previous statistics (Bunster 1951) gave 20% of pregnancies but only 10% of children live. Salpingostomy by foreign gynecologists has 18% of children living but the author has never achieved positive results. Using tubes and stems polyethylene has no reason to be in implementations tube uterine as demonstrated by the low success rate (12%) obtained by Rock et al in US compared to 33% obtained by us we use not say material.